2019
DOI: 10.1111/bdi.12815
|View full text |Cite
|
Sign up to set email alerts
|

A linkage and exome study implicates rare variants of KANK4 and CAP2 in bipolar disorder in a multiplex family

Abstract: Objectives Bipolar disorder (BD) is a neuropsychiatric disorder with a complex pattern of inheritance. Although many genetic studies have been conducted on BD, its genetic correlates remain uncertain. This study was aimed at  identifying the genetic underpinnings of the disorder in an Indian family, which has been under comprehensive clinical evaluation and follow‐up for over 12 years. Methods We analysed a four‐generation family with several of its members diagnosed for BD employing a combination of genetic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The authors suggested that KANK4 and CAP2, which are also expressed in the brain, alone or together are involved in bipolar disorder in the investigated family. 71 In their 2020 publication, Forstner et al described their findings from WES of 81 patients with bipolar disorder from 23 Spanish and four German multigenerational, multiply affected families (three members from each family). The analysis considered only variants shared by all three investigated family members.…”
Section: Polygenicity and Polygenic Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that KANK4 and CAP2, which are also expressed in the brain, alone or together are involved in bipolar disorder in the investigated family. 71 In their 2020 publication, Forstner et al described their findings from WES of 81 patients with bipolar disorder from 23 Spanish and four German multigenerational, multiply affected families (three members from each family). The analysis considered only variants shared by all three investigated family members.…”
Section: Polygenicity and Polygenic Scoresmentioning
confidence: 99%
“…The authors suggested that KANK4 and CAP2 , which are also expressed in the brain, alone or together are involved in bipolar disorder in the investigated family. 71 …”
Section: Wesmentioning
confidence: 99%
“…Therefore, it is also essential to investigate variants shared among patients in order to elucidate the association between transmitted variants and SCZ. Indeed, several sequencing studies have focused on shared variants associated with bipolar disorder [ 18 , 19 ] and autism spectrum disorder [ 20 , 21 ] in patients in the same multiplex family. A previous WES study of SCZ multiplex families demonstrated that several loci could potentially affect synaptic plasticity and neurocognitive performance [ 22 ] and that variants in genes related to metabotropic glutamate receptor 5 (mGlu5) are more common in affected family members [ 23 ].…”
Section: Introductionmentioning
confidence: 99%